ENTRE SÚPLICA E LUTA: ações de viúvas e outros parentes de militares cearenses da “Guerra do Paraguai” (1865-1870) - Souza, Maria Regina Santos de (Outros Tempos: Pesquisa em Foco - História, 2009)
This article has for purpose to show to which the faced difficulties, mainly for the widowers of died pertaining to the state of Ceará military in the war of Paraguay, when they had petitioned next to the Imperial State the pensions of its beings cut with a scythe in combats. Also we analyze which the treatments given for the imperial authorities to these women.